(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
The Federal Constitution has allocated a special place for Islam and Malays without forsaking the interests of other religions and races as the manifestation of the long-agreed Social Contract. Nonetheless, sparks of tension could be seen surfacing after the 14th General Election, allowing sensitive issues especially related to religions and races to materialize. Hence, Rahmatan lil ’Alamin (mercy for all, RLA) was introduced as a means to harmoniously create an inclusive multicultural society. This research identifies the true definition of this concept according to the Federal Constitution through the lens of discussions between Muslim scholars and the constitution itself. The findings were then analysed inductively to encapsulate the definition based on the constitution. A clear understanding and acknowledgement of the special place for Islam in Federal Constitution is key to generate a more harmonious and sensible multi-racial and multi-religious society. The values of RLA should be instilled through making the safeguarding of the place of Islam in Malaysia the focal theme. Keywords: Islam, Rahmatan lil ’Alamin, multiculturality, Federal Constitution